Exploring the effectiveness of green marketing strategies in hospitality - Kim, Woo-Hyuk (Kansas State University, 2018)
This experimental study explores how different marketing tactics, such as advertising types, message appeals, and social norms, influence attitude toward the advertisement, attitude toward the convention, and pro-environmental intention. This research has three objectives: to determine how message types in green advertising affect attitudes and intentions, to examine how message appeals in green advertising affect attitudes and intentions, and to investigate the role of social norms in green advertising in the formation of those attitudes and intentions. To examine the effects of message type, message appeals, and social norms on convention attendees’ behavioral intentions toward such a convention, a 2 (message type) x 2 (message appeals) x 2 (social norms) experimental design was adopted. This was chosen given its recognized ability to clarify associative relationships by enhancing internal validity and the robustness of findings. Several hypotheses were tested with a sample of convention attendees from the United States using Amazon Mechanical Turk. Specific findings from this study include that fact that green marketing messages combining verbal claims and visual claims were significantly more effective than messages using verbal claims only. Additionally, messages with emotional appeals were significantly more effective than ones with rational appeals and messages with injunctive norm claims were significantly more effective than ones with descriptive norm claims. As the first study of its kind to empirically investigate the use of green advertising in the context of conventions, this research involved several novel applications of various theories and a conceptual model. This study utilizes research from several disciplines whose examples can inform green marketing strategies in the convention industry. At the end, the researcher discusses the possible implications of its own findings for the convention industry in addition to its segment in the broader hospitality industry in the United States.
Keywords: Message appeals; Social norms; Green marketing; Advertising